Value of routine stool testing for pathogenic bacteria in the evaluation of symptomatic patients with ileal pouches. (24th November 2017) - Singh, Amandeep; Ashburn, Jean; Kochhar, Gursimran; Lopez, Rocio; Hull, Tracy L; Shen, Bo
Abstract: Background: In symptomatic patients with an ileal pouch, stool studies are often sent to diagnose enteric pathogens. Aim of this study is to find the value of routine stool studies in the evaluation of symptomatic patients and the clinical implications of such pathogens in patients with ileal pouches. Methods: Consecutive ileal pouch-anal anastomosis (IPAA) patients who had stool tests out of a 2283-case registry from 2002 to 2015 were included in the study. Patients with positive stool cultures were compared with controls (symptomatic without positive stool culture) in a 1:4 ratio. Response to antibiotic therapy, recurrence rate and rate of hospitalization at 1 and 3 months were assessed. Results: A total of 643 (28%) had stool cultures done and only 1.7% (11/643) were found to be positive for stool cultures. Campylobacter spp. (45%) was the most common pathogen followed by Aeromonas spp. (36%). Non-smokers and patients without any antibiotic use in the last 3 months were found to have higher prevalence of positive stool cultures than controls ( p  < 0.001 and p  = 0.023). Patients with pathogenic bacteria were found to have a higher risk of acute kidney injury (27.3% vs 4.5%, p  = 0.049), hospitalization within 3 months of initial stool testing (36.4% vs 6.8%, p  = 0.009) and mortality (18.2% vs 0%, p  = 0.040). However, there were no statistically significant differences in the clinical outcomes in patients with positive stool cultures who received pathogen-directed therapy. Conclusions: We found that the yield of stool tests for bacterial pathogens in symptomatic pouch patients was extremely low and the treatment of detected pathogens had a minimum impact on the disease course of pouchitis. The clinical utility of routine stool culture in those patients warrants further study.